Derisking the Risk: Ways and Means Financing Versus Austerity Measures in Management of Fiscal Imbalances in Nigeria - Chenge, Andrew Aondohemba (Journal of Finance and Financial Law, 2026)
The purpose of the article. The study analyses two prominent fiscal adjustment measures – Ways and Means financing, and austerity measures – to determine the most appropriate strategy for managing fiscalimbalances and economic crisis in Nigeria. Methodology. Documentary research design was used as the methodology. Data was derived from reports and publications of government agencies. Data analysis was done using mixed methods content analysis. Results of the research. Findings of the study highlighted that Ways and Means financing is justified since it provides the government with short-term funding to cover budgetary deficits. Nevertheless, if Ways and Means is applied without caution, it is likely to induce unchecked spending and money supply surges, resulting in inflation and currency devaluation. The study maintained that fiscal austerity, which advocates a policy of significant decrease in government deficits and stabilization of government debt through either tax hikes, spending cutbacks, or both, is a more effective measure in managing fiscal imbalances in Nigeria.